Study of the yeast cytosolic Hsp70-system in protein homeostasis and life span regulation - Intracellular colocalisation of the chaperone Ssa4-GFP and the metacaspase Mca1-RFP before and after heat stress in a Hsp70-mutant yeast cell strain - Vielfort, Katarina; Andersson, Rebecca; Nyström, Thomas (University of Gothenburg, 2020)
Our study aims to answer the question "Which functions of the Hsp70 class of molecular chaperones are essential for yeast to maintain a standard replicative life span?". To answer this question, we utilised the disparate functions of the Hsp70's Ssa1 and 2 and their paralog Ssa4 in a yeast strain that lacks Ssa1/2 but has an ectopically increased production of Ssa4. We have gathered data on the behaviour of several different markers for protein aggregation under different circumstances, as well as data on proteins from other classes of molecular chaperones. The bulk of the data is in the form of multichannel microscopy images from widefield microscopy, with a few sets of western blots of protein extracts.

Fluorescence microscopy of live yeast cells at mid-exponential growth before and after 30 minutes of heat shock. All strains produce the Hsp70 chaperone protein Ssa4 tagged with GFP (Ssa4-GFP) and the metacaspase Mca1 tagged with RFP (Mca1-RFP).
The dataset was collected through fluorescence microscopy.
The image files are provided in Carl Zeiss Image format (.czi).

Vi har systematiskt studerat vilka funktioner hos de cytosoliska molekylära chaperonerna av klassen Hsp70 hos jäst som krävs för att upprätthålla en normal livslängd.

Fluorescensmikroskopibilder av levande jästceller i mitten av den exponentiella tillväxtfasen, före och efter 30 minuter värmestress. Jästen är odlad i rikt medium (YP) med 2 % glukos som kolkälla. Alla stammar producerar Hsp70 chaperonproteinet Ssa4 taggat med GFP (Ssa4-GFP) och metacaspaset Mca1 taggat med RFP (Mca1-RFP).
Datasetet är insamlat genom fluorescensmikroskopi.
Bildfilerna är i Carl Zeiss Image-format (.czi).
Studier av det cytosoliska Hsp70-systemet från jäst och dess roll i proteinhomeostas och reglering av livslängd - Intracellulär kolokalisering av chaperonet Ssa4-GFP och metacaspaset Mca1-RFP före och efter värmestress i en Hsp70-mutant jäststam
Keywords: Molecular Chaperones; Molekylära chaperoner; HSP70 Heat-Shock Proteins; HSP70-värmechockproteiner; Proteostasis Deficiencies; Proteostasbrist; Cell Biology; Cellbiologi; Microbiology; Mikrobiologi; Cell and Molecular Biology; Cell- och molekylärbiologi; Molecular Biology; Molekylärbiologi